KETIDAKTEPATAN PENGGUNAAN DIKSI DALAM TEKS BERITA DI TVRI KOTA PALU - Nursyamsi S.S., M.Pd. (Multilingual, 2018)
The word or choice of words used in the news text "Lintas Berita" on TVRI Palu still shows a lot of inaccuracy. With regard to diction, the purpose of this study is to describe the inaccuracy of the use of diction and provide a remedial solution to this inaccuracy. Data is obtained by using the refer method and the data analysis technique is descriptive-prescriptive. The results of the study show that diction used in the news text "Cross Central Sulawesi" does not meet the rules of word selection from the aspect of truth and accuracy. Keywords: inaccuracy of diction, news text